An Adaptive Interface Design (AID) for enhanced computer accessibility and rehabilitation. Issue 98 (February 2017) - Lin, Yingzi; Breugelmans, Jeffrey; Iversen, Maura; Schmidt, David
Abstract: This study was aimed at the development of a non-intrusive, biosensor based, Adaptive Interface Design (AID) that utilizes its users' physical abilities (rather than focusing on their disabilities), while simultaneously honoring their integrity and needs. The target users for this study were patients with arthritis in the hand. The AID comprises of eye tracking and data glove technologies, the latter of which will be used to measure the user's physical ability as it translates hand gestures into computer controls. By developing accessible computer interfaces and exploring their use for telerehabilitation purposes, we want to ultimately impact the inclusion and health outcomes of those who experience disability on a daily basis. Highlights: Data Glove for rehabilitation that can measure position and strength. Eye tracker and glove for alternative virtual environment interface. Virtual environment to encourage rehabilitation exercise. User experience used to provide improvements device effectiveness.